Evaluation of Canalis Sinuosus on CBCT Images of Patients Candidate for Dental Implant Treatment in Iranian Population - Ashkan Salari; Farzane Ostovarrad; Shahrzad Banan; Fereshteh Naser Alavi (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To evaluate the frequency, diameter, location and path of canalis sinuosus (CS) on CBCT scans of patients candidate for dental implant treatment. Material and Methods: In this cross-sectional study, 200 CBCT images of the maxilla were evaluated and parameters were assessed: age, gender, the canal presence and diameter, the distance between the CS and the nasal cavity floor (NC), the buccal cortical bone (BC) and the most prominent point of the alveolar ridge crest (RC). Quantitative variables were analyzed with an independent t-test, and qualititative variables were analyzed with chi-squared and McNemer tests (p<0.05). Results: CS was detected on 100 CBCT images in the present study. There were significant relationships between the CS frequency and age and gender; however, there was no significant relationship between CS and the maxillary side. The means of BC, RC, NC and the canal diameter were 9.2±2.19, 15.15±3.13, 8.14±2.43, and 0.99±0.26 mm, respectively. There were significant relationships between the canal diameter, NC and BC with gender. However, there was no significant relationship between RC and gender. Conclusion: Canalis sinuosus was detected, with an approximate diameter of 1 mm, in 50% of the subjects in the incisor–canine area. The use of CBCT for accurate diagnosis of canalis sinuosus is suggested before surgical procedures in the palatal aspect of the anterior maxilla.